MENGUNGKAP PERAN DESA ADAT DALAM PRAKTIK TATA KELOLA LPD DI BALI - I Wayan Sudiana; Ni Made Wisni Arie Pramuki; Ni Wayan Alit Erlinawati; Kadek Dewi Pradnyawati; Putu Nuniek Hutnaleontina (Faculty of Economics and Business, Universitas Warmadewa, 2025)
Village Credit Institution (VCI) is a microfinance institution that is specifically in Bali Province and has a role to maintain the existence of traditional village institutions that are the last bastion of Balinese culture. The existence of VCI supported by the traditional village community (krama desa) has a very strategic function, namely to spur rural economic development, prevent farmers from the trap of ijon from middlemen, and at the same time maintain the local wisdom of the traditional village. The purpose of VCI is to help traditional villages carry out their cultural functions. VCI has been proven to be able to improve the economic, social, and cultural conditions of the community. In fact, not all VCIs are able to develop sustainably. One of the factors causing this problem is the lack of awareness to realize governance practices in preventing conflicts between administrators and village communities as VCI owners. Good governance practices must meet the principles of transparency, accountability, responsibility, independence, and fairness. Therefore, it is important to review the governance practices of custom-based VCIs. This research was conducted at LPD Kerobokan. Data analysis with a qualitative descriptive approach. The main findings of this study confirm that customary villages play a central role in the management of Village Credit Institutions (VCI). The study shows that the structure and decision-making process based on customary village deliberations provide strong legitimacy to VCI policies and practices. This not only increases transparency but also strengthens community trust in VCI. The importance of synergy between custom and governance in VCI management by strengthening the role of customary villages and integrating local values ??in governance.